Managing adaption of community open spaces in semi-arid region, Katsina Nigeria - Gidado, Usman Muhammad (2022)
Desertification is one of the most serious and alarming social and environmental concerns we face today. Open spaces are recognized as a critical component of the landscape in semi-arid rural communities since they serve as the site of socio-cultural and economic activities. It is important to keep an organized and well-managed open space in northern Nigeria to ensure that they accommodate the cultural and ethical values of the communities they serve. Site observations and in-depth interviews with community leaders were conducted to explore and investigate the community's adaptation management strategies (local approaches) for the sustainability of open spaces in hosting socio-cultural events in a semi-arid region of northern Nigeria. The goal was to produce adaption management strategies that would assure the continuity of community open spaces while preserving socio-cultural activities. The results were analyzed using ATLAS Ti for data processing, with the real analysis taking place during the reporting stage. The results were reported using simple statistical techniques. The study reveals the typology, improved concept, and functional categorization of community open spaces. It also investigates adaptation management strategies and methods. Additionally, it was revealed several adaptation strategies and techniques for community open spaces depended heavily on indigenous knowledge. The report recommends using local knowledge and indigenous materials to manage open spaces that can sustainably host the community's socio-cultural and economic activities. The findings of this study will serve as a guide for decision-makers, resource planners, policy-makers, and tourists. It will also guarantee orderly community utilization of open spaces and improve their sustainability.